2021
DOI: 10.1007/s00268-021-06350-7
|View full text |Cite
|
Sign up to set email alerts
|

Work Characteristics of Acute Care Surgeons at a Swiss Tertiary Care Hospital: A Prospective One‐Month Snapshot Study

Abstract: Background Multiple acute care surgery (ACS) working models have been implemented. To optimize resources and on-call rosters, knowledge about work characteristics is required. Therefore, this study aimed to investigate the daily work characteristics of ACS surgeons at a Swiss tertiary care hospital. Methods Single-center prospective snapshot study. In February 2020, ACS fellows prospectively recorded their work characteristics, case volume and surgical cas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The responsibilities of the surgical on-call team are multiple and highly relevant to the overall hospital system [ 20 ]. Besides the surgical skills in emergency and elective cases, knowledge regarding initial evaluation of acute surgical patients, ICU relevant topics and non-operative treatment strategies are required to overcome this unique role of in-house troubleshooting.…”
Section: Discussionmentioning
confidence: 99%
“…The responsibilities of the surgical on-call team are multiple and highly relevant to the overall hospital system [ 20 ]. Besides the surgical skills in emergency and elective cases, knowledge regarding initial evaluation of acute surgical patients, ICU relevant topics and non-operative treatment strategies are required to overcome this unique role of in-house troubleshooting.…”
Section: Discussionmentioning
confidence: 99%
“…The responsibilities of the surgical on-call team are multiple and highly relevant to the overall hospital system [20]. Besides the surgical skills in emergency and elective cases, knowledge regarding initial evaluation of acute surgical patients, ICU relevant topics and non-operative treatment strategies are required to overcome this unique role of inhouse troubleshooting.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning in 2005, the maximum allowable number of working hours was capped at 50 for both residents and attendings [25]. A total of six studies were found that sought to determine the effects of these changes [25][26][27][28][29][30].…”
Section: Working Conditions In Switzerlandmentioning
confidence: 99%
“…Finally, in order to form a more complete picture of daily clinical practice, Di Pietro et al analysed the variety of tasks completed by trainees during their time on call [30]. A relatively even distribution was observed, with participants dedicating approximately 1/3 of their time to operating, rounding on patients, and completing administrative tasks.…”
Section: Working Conditions In Switzerlandmentioning
confidence: 99%